Teachers' Views on Canva-Assisted Flashcards as Learning Media on Multiplication Material For Elementary School Students - Sri Wahyuni; Tri Murwaningsih; Joko Daryanto (Teknodika, 2025)
The low creative thinking skills of students in Indonesia, as reflected in the low scores on the Programme for International Student Assessment (PISA), indicate significant challenges in the education system. Conventional learning media that are less interactive are one of the factors that hinder student engagement and the development of their creativity. This study aims to explore teachers' views on the development of Canva-assisted flashcards as interactive learning media for multiplication material in elementary schools. This study uses a descriptive qualitative method, with the subjects of the study being teachers at SD Negeri 2 Pondok, Wonogiri Regency, who were selected purposively. Data collection techniques include semi-structured interviews, non-participatory observation, and document analysis. Data were analyzed using the Miles & Huberman interactive analysis model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that teachers are aware of the limitations of conventional learning media and consider Canva-assisted flashcards as an innovative solution. This media is considered capable of increasing student engagement, facilitating the understanding of multiplication concepts, and supporting creative thinking skills. These findings emphasize the importance of developing technology-based learning media to support 21st-century education.